Land Use/Cover Change in the Middle Reaches of the Heihe River Basin over 2000-2011 and Its Implications for Sustainable Water Resource Management. - Xiaoli Hu; Ling Lu; Xin Li; Jianhua Wang; Ming Guo (PLoS ONE, 2015)
The Heihe River Basin (HRB) is a typical arid inland river basin in northwestern China. From the 1960s to the 1990s, the downstream flow in the HRB declined as a result of large, artificial changes in the distribution of water and land and a lack of effective water resource management. Consequently, the ecosystems of the lower reaches of the basin substantially deteriorated. To restore these degraded ecosystems, the Ecological Water Diversion Project (EWDP) was initiated by the Chinese government in 2000. The project led to agricultural and ecological changes in the middle reaches of the basin. In this study, we present three datasets of land use/cover in the middle reaches of the HRB derived from Landsat TM/ETM+ images in 2000, 2007 and 2011. We used these data to investigate changes in land use/cover between 2000 and 2011 and the implications for sustainable water resource management. The results show that the most significant land use/cover change in the middle reaches of the HRB was the continuous expansion of farmland for economic interests. From 2000 to 2011, the farmland area increased by 12.01%. The farmland expansion increased the water resource stress; thus, groundwater was over-extracted and the ecosystem was degraded in particular areas. Both consequences are negative and potentially threaten the sustainability of the middle reaches of the HRB and the entire river basin. Local governments should therefore improve the management of water resources, particularly groundwater management, and should strictly control farmland reclamation. Then, water resources could be ecologically and socioeconomically sustained, and the balance between upstream and downstream water demands could be ensured. The results of this study can also serve as a reference for the sustainable management of water resources in other arid inland river basins.